Driving school program to strengthening anti-corruption education within the integrity zone policy - Suyadi, Suyadi; Nuryana, Zalik; Asmorojati, Anom Wahyu; Yudhana, Anton (Institute of Advanced Engineering and Science, 2025)
For an extended period, education institutions have functioned independently, resulting in a notable disparity in educational quality. The Merdeka Belajar Kampus Merdeka (MBKM) promotes collaboration between educational institutions and schools, with the aim of serving as mentors for joint program development. This groundbreaking research delves deeply into the pivotal roles played by both lecturers and students within the MBKM program. They emerge as mentors in the crusade for implementing anti-corruption education within the dynamic context of Sekolah Penggerak, also known as the driving school program (DSP). Conducted as a qualitative descriptive study, this research draws its data from the collaborative efforts between higher education institutions and schools in developing anti-corruption education, leading to recognition from the Indonesian Corruption Eradication Commission (KPK-RI). The data collection process unfolds through a meticulously orchestrated combination of observations, in-depth interviews, and thorough documentation. The findings of this study are nothing short of transformative, as they underscore how the active involvement of MBKM’s lecturers and students in anti-corruption education serves as a potent catalyst, reinforcing the integrity zone policy within the DSP program. This seamless integration of anti-corruption education with Islamic education, encompassing profound concepts like riswah (bribery), ghulul (betrayal), and mukabarah-ghasab (seizing), represents a paradigm shift in pedagogical strategies.